Discourse Cohesion Markers and Pragmatic Tones in Oprah Winfrey’s(2008) Motivational Speech - Reem Maghrabi (Journal of Arts, Literature, Humanities and Social Sciences, 2022)
This study examined how forms and functions of intonation discourse markers could be employed to deliver the pragmatic force of motivation in Oprah Winfrey’s (2008) Speech at Stanford’s Commencement Ceremony. It also explored the most recurring tones as classified by Well's (2006) in relation to Searle's (1969) speech act theory and Halliday and Hasan's (1976) discourse cohesion categorizations, with specific reference to lexical repetition as a discourse cohesive device. The findings revealed that the most frequently used tones were the rising and falling tones. The extensive use of these tones was due to the nature of illocutionary force investigated, which was motivation,  to assert strong feelings of excitement. The rising tone was used mostly  as a discourse marker of introducing and contrasting information and as a cohesive device for enhancing ideas, while the falling tone was used mostly as a discourse marker of finishing and concluding and as a cohesive device for extending ideas.